Learner Autonomy during COVID-19: The Case of Moroccan EFL Undergraduates com - Insaf Khoudri; Mohammed Zeriouh (Yayasan Visi Intan Permata, 2023)
Learner autonomy is one of the predictors of academic performance. Many researchers have argued that moving from secondary to higher school is a big transition. Shifting the focus from teacher-centeredness to learner-centeredness, learners in higher school display less reliance on their teachers to carry on their learning. Throughout this process, learners develop their autonomy and boost their independence. However, numerous studies revealed that most students are unaware of this shift. The purpose of this paper is to assess the autonomy of Moroccan EFL undergraduate students during the Covid-19 pandemic. Equally, this study aims at developing awareness of some strategies and techniques students use to increase their autonomy and self-independence. To achieve this purpose, the study employed a quantitative approach. A Likert scale-based questionnaire was administered to 100 (55 males and 45 females) EFL Moroccan undergraduate students. The research data was generated and analyzed using SPSS. Statistical analysis revealed that during the Covid-19 pandemic (69%) of EFL students were not aware of their role as independent and autonomous learners. Likewise, only (30%) of them were involved in syllabus design. Nevertheless (49%) of EFL students revealed their readiness to be part of decision-making concerning the teaching-learning process. The study results suggest that the use of the internet, self-managerial skills, peer and teacher collaboration are among the effective strategies students employ to increase their autonomy and self-independence alike.